2018
DOI: 10.1002/ijc.31736
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and biological function of WD repeat domain 54 as an oncogene in colorectal cancer

Abstract: In recent years, protein-protein interactions have become an attractive candidate for identifying biomarkers and drug targets for various diseases. However, WD40 repeat (WDR) domain proteins, some of the most abundant mediators of protein interactions, are largely unexplored. In this study, 57 of 361 known WDR proteins were identified as hub nodes, and a hub (WDR54) with elevated mRNA in colorectal cancer (CRC) was selected for further study. Immunohistochemistry of specimens from 945 patients confirmed the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
(139 reference statements)
1
14
0
Order By: Relevance
“…Previous studies have reported that mutations of WDR34 mRNA are primarily associated with short-rib polydactyly syndrome type III and severe asphyxiating thoracic dysplasia (8,9). Loss-of-function mutations of FBXW7, another WDR protein, have been identified in colorectal cancer (18%), uterine endometrial carcinoma (15%) and uterine carcinosarcoma (40%), suggesting that the interactions between FBXW7 and its substrates are interrupted by disrupting the structural integrity of the WDR domain (47,48). Notably, compounds targeting the WDR domain of FBXW7 are expected to antagonize binding of cyclin E and phenocopy the oncogenic effect of mutations that are recurrent in cancer (47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that mutations of WDR34 mRNA are primarily associated with short-rib polydactyly syndrome type III and severe asphyxiating thoracic dysplasia (8,9). Loss-of-function mutations of FBXW7, another WDR protein, have been identified in colorectal cancer (18%), uterine endometrial carcinoma (15%) and uterine carcinosarcoma (40%), suggesting that the interactions between FBXW7 and its substrates are interrupted by disrupting the structural integrity of the WDR domain (47,48). Notably, compounds targeting the WDR domain of FBXW7 are expected to antagonize binding of cyclin E and phenocopy the oncogenic effect of mutations that are recurrent in cancer (47).…”
Section: Discussionmentioning
confidence: 99%
“…WD repeats are minimally conserved regions of about 40 amino acids typically bracketed by tryptophan-aspartic acid (WD) and glycine-histidine (GH; Raab et al, 2010) that proved to promote the formation of heterotrimeric or polyprotein complexes. WDR12, a member of WDRs, regulates a wide variety of physiological functions, including muscle differentiation, cardiac growth, T-regulatory cell function, and neuronal disorders (Higa et al, 2006;Xu et al, 2014;Yuan et al, 2019). Recent studies have shown that WDR12 is an essential factor in tumorigenesis and plays a dual role in different cancers (Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As a protein–protein scaffold, the WD40 protein plays an important role in signal transduction, RNA synthesis and processing, cell cycle regulation, apoptosis and so on 6 . Studies have shown that the WD40 protein is abnormally expressed in many kinds of human malignant tumours, such as liver cancer, colorectal cancer, lung cancer, oesophageal cancer, breast cancer, cervical cancer and so on 7–10 . WDR48 has been reported to regulate the activities of ubiquitin‐specific proteases USP1, USP12 and USP46.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Studies have shown that the WD40 protein is abnormally expressed in many kinds of human malignant tumours, such as liver cancer, colorectal cancer, lung cancer, oesophageal cancer, breast cancer, cervical cancer and so on. 7 , 8 , 9 , 10 WDR48 has been reported to regulate the activities of ubiquitin‐specific proteases USP1, USP12 and USP46. The WDR48–USP1 complex acts as a regulator during DNA damage, especially in translation synthesis and Fanconi anaemia pathway.…”
Section: Introductionmentioning
confidence: 99%